Mismatch in receiver responses to multimodal signals in a diurnal gecko. (January 2019) - Kabir, Md Shakilur; Radhika, Venkatesan; Thaker, Maria
Abstract : Multimodal signals are used by many animals for intraspecific communication and can provide information about sex identity as well as quality of the signaller. In diurnal geckos of the genus Cnemaspis, chromatic colour patches in males evolved after chemical secretions, providing us with an opportunity to examine the utility of evolving multimodality. We quantified signal components and receiver responses in Cnemaspis mysoriensis to determine the relative importance of chemical and visual traits for intraspecific communication. Digital imagery and spectrophotometry of lizards revealed the presence of two distinct male morphs (yellow-gular and white-gular) and one female form (white-gular). All males, but no females, had yellow eye rims. Characterization of chemical secretions from the ventral precloacal and femoral glands of all lizard forms revealed no differences between male morphs. However, all males differed from females in a few key compounds. We then exposed lizards to only chemical stimuli, only visual stimuli, or both chemical and visual stimuli of conspecific males and females. We found that females were responsive to the chemical stimuli alone as well as the multimodal stimuli of males, whereas males were only responsive to the multimodal stimuli of other males. Neither chemical or visual components of females elicited a response from conspecifics. Thus, while the chemical secretions of males are sufficient for females to elicit a response, multimodal stimuli are necessary for males to respond. Based on variation in signalling traits and receiver responses, we conclude that: (1) chemical secretions signal both sex identity and male quality; (2) eye rim colour encodes information about sex identity; and (3) gular colour in males is probably not a redundant trait, providing some information to males, but not females. We conclude that the secondary evolution of visual signals in C. mysoriensis therefore enhances male–male social interactions and not communication in general. Highlights: We studied the utility of multimodal signals in C. mysoriensis. Sexes differ in chemical traits as well as some visual traits. Males have two morphs that are distinguishable visually, but not chemically. Females use chemical stimuli to communicate, but males require multimodal stimuli. Visual signals enhance male-male interactions and not overall communication.